2015
DOI: 10.3168/jds.2014-9137
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic antimicrobial susceptibility and occurrence of selected resistance genes in gram-positive mastitis pathogens isolated from Wisconsin dairy cows

Abstract: In the United States, few intramammary antimicrobials exist that are approved for treatment of bovine mastitis; thus, ensuring judicious use of these products is a priority. The objectives of this study were to determine phenotypic susceptibility and presence of selected antimicrobial resistance genes from staphylococci, streptococci, and streptococcal-like organisms recovered from cases of clinical mastitis occurring in cows on large Wisconsin farms. Staphylococcus aureus (n=35 from 19 herds), coagulase-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
38
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 52 publications
12
38
3
5
Order By: Relevance
“…Likewise, mecA gene (resistance to β-lactam antibiotics; Wendlandt et al, 2013) was identified in >15 and 70% of S. aureus and NAS isolates, respectively. Prevalence of mecA among Staphylococcus isolates in this study was higher on these Chinese dairy farms than in CM isolates from other studies (Frey et al, 2013;Ruegg et al, 2015). This high prevalence of blaZ and mecA and potential resistance to β-lactam antibiotics in Chinese bovine Staphylococcus isolates highlighted a decisive point in the use of these antimicrobials, commonly used in mastitis treatment, in the dairy industry in China and other countries.…”
Section: Discussionmentioning
confidence: 41%
“…Likewise, mecA gene (resistance to β-lactam antibiotics; Wendlandt et al, 2013) was identified in >15 and 70% of S. aureus and NAS isolates, respectively. Prevalence of mecA among Staphylococcus isolates in this study was higher on these Chinese dairy farms than in CM isolates from other studies (Frey et al, 2013;Ruegg et al, 2015). This high prevalence of blaZ and mecA and potential resistance to β-lactam antibiotics in Chinese bovine Staphylococcus isolates highlighted a decisive point in the use of these antimicrobials, commonly used in mastitis treatment, in the dairy industry in China and other countries.…”
Section: Discussionmentioning
confidence: 41%
“…The presence of both genes has been previously reported in bovine and human Streptococcus spp. isolates (53, 70). In general, associations between the phenotypic and genotypic characteristics were observed for a limited number of antibiotics for both pathogens (Table 3; Table S3 in Supplementary Material; P  < 0.10).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the issue of resistant or multiresistant MCP such as methicillin‐resistant S. aureus (MRSA) seems to play a subordinate role in dairy industry (Erskine et al., ; Kreausukon et al., ; Oliver, Murinda, & Jayarao, ; Pol & Ruegg, ; Schröder, Hoedemaker, & Klein, ; Tenhagen et al., ). However, the number of studies reporting of enhanced emergence of AMR increases (da Costa Krewer et al., ; Ding et al., ; Fairbrother et al., ; Jagielski et al., ; Petrovski et al., ; Ruegg, Oliveira, Jin, & Okwumabua, ; Saini, McClure, Scholl, DeVries, & Barkema, ; Spohr et al., ).…”
Section: Mastitis Management—therapeutic Measuresmentioning
confidence: 99%